Subjective Age and Falls in Older Age: Evidence From Two Longitudinal Cohorts. (21st July 2022) - Fundenberger, Hervé; Stephan, Yannick; Terracciano, Antonio; Dupré, Caroline; Bongue, Bienvenu; Hupin, David; Barth, Nathalie; Canada, Brice
Abstract: Objectives: Falls are a common and serious health problem. The present study examined the association between subjective age (i.e., feeling younger or older than one's chronological age) and falls in 2 large national samples. Method: Participants aged 65–105 years old were drawn from the National Health and Aging Trends Study (NHATS) and the Health and Retirement Study (HRS). Data on falls, subjective age, and demographic factors were available from 2, 382 participants in HRS and 3, 449 in NHATS. Falls were tracked for up to 8 (HRS) and 7 (NHATS) years. Results: Cox regression analyses that included demographic covariates indicated that older subjective age increased the risk of falling in HRS (hazard ratio [HR] = 1.17, 95% confidence interval [CI] = 1.08–1.27) and in NHATS (HR = 1.06, 95% CI = 1.00–1.13). When compared to people who felt younger, people who reported an older subjective age had a higher risk of fall (HRS: HR = 1.65, 95% CI = 1.33–2.04; NHATS: HR = 1.44, 95% CI = 1.15–1.79). The associations remained significant after accounting for depressive symptoms, handgrip strength, chronic diseases, and cognitive impairment in HRS only. Discussion: These results confirm the role of subjective age as an important health marker in the aging population. Subjective age assessment can help identify individuals at greater risk of falls.